Selection of Raw Material Suppliers For Yarn Based on Sustainable Supply Chain Management Criteria Using Fuzzy Analytical Hierarchy Process (FAHP) and TOPSIS Methods at PT XYZ - Yulia Sari, Alma Dwi; Pulansari, Farida; Nugraha, Isna (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
The industrial revolution and mass production directly increased human productivity and significantly impacted the environment. Amid these environmental problems, companies created environmentally friendly production strategies and prioritized economic factors (profit) and how they impact the social environment. This makes sustainable supply chain management in Sustainable Supplier Selection (SSS) increasingly in demand because it can affect the company's environmental performance. Companies that can improve their environmental and social performance will be able to increase their competitive advantage and impact, increasing revenue, market share, and a more positive green image of the company. There is no research on sustainable supplier selection in the sarong industry, especially in Indonesia. Therefore, research is needed on the sector because it dramatically affects environmental performance. One of the companies engaged in the sarong industry is XYZ company. This study aims to evaluate Supplier performance based on sustainable aspects (economic, environmental, social) using the cut-off point method for selecting sub-criteria, FAHP for assigning sub-criteria weights, and TOPSIS for ranking Suppliers based on predetermined sub-criteria. As a result of data processing, suppliers are ranked based on their preferences. As a result, Supplier 2 (S2) ranked first with a preference value of 0.9210, followed by Supplier 1 (S1) with a preference value of 0.7514, Supplier 3 (S3) with a preference value of 0.3166, and Supplier 4 (S4) with a preference value of 0.00019.